Gamma glutamyl transpeptidase levels in arthritis: a correlation with clinical and laboratory indices of disease activity. Issue 5 (October 1978) - Lowe, J R; Pickup, M E; Dixon, J S; Leatham, P A; Rhind, V M; Wright, V; Downie, W W
Abstract : Gamma glutamyl transpeptidase (GGTP) was measured in 62 patients with rheumatoid arthritis (RA) and 27 with osteoarthrosis (OA). The values for GGTP were significantly higher in the subjects with RA compared with the OA group. The prevalence of elevation of GGTP was higher in the RA subjects (77%) than in the OA patients (33%). Levels of GGTP correlated significantly with a number of objective indices of activity of RA in a separate group of 28 patients. Following treatment with penicillamine, GGTP levels showed a significant drop towards normal levels.